Child to adult body mass index in the 1958 British birth cohort: associations with parental obesity. Issue 5 (1st November 1997) - Lake, Julie K; Power, Chris; Cole, Tim J
Abstract : OBJECTIVES: To assess relations between the adiposity of children and their parents and to establish whether tracking of adiposity from childhood to adulthood varies according to the parental body mass index (BMI). METHODS: Longitudinal data from the 1958 British birth cohort study were used (6540 men and 6207 women). The height and weight of the study subjects were measured at 7, 11, 16, 23 (self reported), and 33 years. Parental height and weight were self reported when their children were 11 years old. The children were classified into six parental BMI (weight/height 2 ) groups. RESULTS: At each age of follow up the mean BMI of the children increased as the parental BMI increased. Higher risks of adult (33 year) obesity were evident among children with overweight or obese parents: the odds for sons and daughters with two obese parents (compared with those with both parents of normal BMI) were 8.4 and 6.8, respectively. The children of two obese parents also showed the strongest child to adult tracking of BMI as indicated by the correlation between ages 7 and 33 ( r = 0.46, 0.54, sons and daughters, respectively). CONCLUSIONS: The children of obese and overweight parents have an increased risk of obesity. Subjects with two obese parents are fatter in childhood and also show a stronger pattern of tracking from childhood to adulthood. As the prevalence of parental obesity increases in the general population the extent of child to adult tracking of BMI is likely to strengthen.